MANAGEMENT STRATEGY OF THE ROYAL PITA MAHA AS A TOURISM ACCOMMODATION IN UBUD, GIANYAR REGENCY - Anak Agung Istri Wahyu Bira Dewi; I Gusti Made Widya Sena; I Nyoman Piartha (Adisam Publisher, 2025)
Tourism serves as a strategic sector for Indonesia’s economic growth, with Bali standing out as a leading destination that has rapidly recovered after the pandemic. Ubud, as the cultural and artistic center of Bali, continues to develop through the contribution of culturally oriented accommodations such as The Royal Pita Maha. This study analyzes the resort’s management strategies in maintaining sustainability and competitiveness amid the highly competitive tourism industry. Employing a descriptive qualitative approach through observation, interviews, documentation, and literature study, the data were analyzed using the SWOT framework. The findings reveal that the POAC-based management strategy implemented by the resort emphasizing cultural and nature-based visitor experiences is effective in enhancing guest satisfaction and loyalty while supporting sustainable tourism development in Ubud.